2016
DOI: 10.1111/1460-6984.12270
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic transfer effects after phonologically based cognate therapy in a case of multilingual specific language impairment (SLI)

Abstract: Cross-linguistic transfer effects were evident during therapy and after therapy had finished and the effects were maintained 1 month post-treatment. Both the native language (Bulgarian) and the dominant language (Greek) benefitted equally from the treatment of cognates in English. Generalization to non-treatment words was evident, predominantly for English. The results suggest that cognates can indeed be used successfully as a WFD intervention strategy for multilingual children with SLI with lasting effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
(75 reference statements)
0
27
0
Order By: Relevance
“…This is because it implies that linguistic distance is not a monolithic construct but is a gradable one, and that its impact on processing is commensurate with degree of distance. Moreover, these results show that the impact of linguistic distance on processing is quantifiable and may, hence, be reliably measured (Kambanaros, Michaelides, & Grohmann, 2017).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is because it implies that linguistic distance is not a monolithic construct but is a gradable one, and that its impact on processing is commensurate with degree of distance. Moreover, these results show that the impact of linguistic distance on processing is quantifiable and may, hence, be reliably measured (Kambanaros, Michaelides, & Grohmann, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Future research should also test the role of awareness of cognates and of cognate training in bootstrapping vocabulary acquisition. Also, whether cognate training would have the same impact on phonological representations in bilingual contexts (e.g., Kambanaros et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This result may intuitively suggest that such cognate items may be useful for clinical diagnosis and treatment of bilingual children (e.g., Kambanaros et al . ). Unfortunately, with the few cognate items available in the current set, there was no reliable difference between the TLD and DLD groups, both among the monolingual and among the bilingual children, on these items.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of speechlanguage intervention, exposure to a cognate in one language may increase vocabulary across both languages, which would grant cognates a baseline advantage in treatment. To date, one study has reported the effects of a naming treatment containing only cognates that was administered to a multilingual 8-year-old girl with SLI (Kambanaros, Michaelides, & Grohmann, 2017). At baseline, the child did not demonstrate an advantage for cognate items (Kambanaros et al, 2015).…”
Section: Cognates As Intervention Targetsmentioning
confidence: 99%